The Effect of Colchicine on The Genotypic and Phenotypic Diversity of The Aglaonema Plant (Aglaonema cochinense Schoot Var. Lady Valentine) - Melvi Wahyu Angraini Nst; Hot Setiado; Revandy Iskandar M. Damanik (Universitas Sumatera Utara, 2018)
The aim of the research was to determine the effect of colchicine on the genotypic and phenotypic diversity of the Aglaonema plant. The research was conducted at the greenhouse of Faculty of Agriculture, North Sumatera University Medan with 32 meters altitude, from January 2017 to May 2017. The plant materials were immersed in 5 ppm and 10 ppm colchicine for 3 and 6 hours. The result showed that the colchicine concentration significantly affected the increased plant height. The plants were immersed in 10 ppm colhicine for 6 hours showed the morphological and chromosomal difference compared with the control and other treatment. Keywords: aglaonema, colchicine, duration of immersio, ghenotypic diversity, phenotypic diversity.